Belarus - Industrial Performance Before and During the Global Crisis : Belarus Economic Policy Notes : Note No. 2 - World Bank (World Bank, 2012)
This note attempts to analyze and tentatively answer these questions by focusing on the drivers of growth and productivity, labor markets and enterprise restructuring, as well as the state system of enterprise support, which is key to understanding the interplay between the state and the economy in Belarus. The period of analysis covers 2004-08 with appropriate references to the previous periods and comparisons with Russia and/or other Commonwealth of Independent States (CIS) countries. The final section explores the Belarus's industrial performance in the period of the global crisis (late 2008-09) and reviews the government's policies that have been largely responsible for a relatively mild effect of the crisis on economic dynamics in the country. The analysis is based on the official statistics provided to the team by the National Statistics Committee (Belstat), National Bank, and various ministries, as well as statistics from other national and international statistical sources. In addition, the analysis benefited from the data provided by various enterprise surveys undertaken by the Research Institute by the Ministry of Economy (RIME) and from two sector case studies (in machinery and dairy sub-sectors). Belarus has weathered the crisis so far better than most of its neighbors, in part due to the government policies to boost domestic demand in a predominantly state-owned and controlled economy. This was achieved at a considerable macroeconomic cost. The country's ability to sustain possible future shocks declined, and macroeconomic risks increased. The crisis has further exposed risks associated with the Government of Belarus (GOB) practice of heavy reliance on administratively set targets for large and medium-size enterprises, especially targets for output and average wage growth.